Development of roundabout delay models using traffic simulation programs: a case study at Al-Mansour City, Iraq - Essa, Alla Jaber; Amiruddin Ismail,; Jehad, Ali Emad; Hussein, Ameer Abdul Adheem; Khalaf, Abdullah Hayal; Yahia, Hussin A.M. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Due to the increased number of vehicles, shopping centers and rapid growth population of Al-Mansour city, daily trips have been increasing besides generating traffic congestion in major roundabouts in the city. Those will make developing an imperial delay model in roundabouts important due to the traffic and geometric influences. Therefore, two major roundabouts have been selected in the city to be taken as a case study. Geometric features for the selected roundabouts have been measured accurately by satellite images via ArcGIS. Traffic and geometric data analysis indicate that both are significantly important on delay models. The delay time produced by SIDRA and SYNCHRO has been compared with the delay time measured from the field. A significant difference in delay for roundabouts is noticed. This difference could be attributed to the difference in driver behaviour. Ideal saturation flow is the main factor related to driver behaviour, so it adjusted to be the average of the saturation flow measured from the field (2200 vphgpl).